MRI features of combined hepatocellular-cholangiocarcinoma. - Majeed, Noor Fatima; Macey, Mathew; Amirfarzan, Marta Braschi; Sharifi, Sheida; Wortman, Jeremy R (Abdominal Radiology, 2025)
Combined hepatocellular cholangiocarcinoma (cHCC-CCA) is a rare liver tumor which has a more aggressive behavior and worse survival outcome than hepatocellular carcinoma (HCC), with a prognosis similar to that of intrahepatic cholangiocarcinoma (iCCA). With limited literature on the appearance of this tumor on MRI, it remains a diagnostic challenge. In this review, we looked at the currently described MRI findings in this uncommon entity. Based on studies conducted to date, a mixed pattern at imaging has demonstrated the highest specificity, seen as a combination of areas showing progressive enhancement of the lesion, arterial enhancement with washout, and areas of arterial enhancement without washout and/or hypovascularity. Tumor markers may aid in identification, particularly in cases where the imaging appearance mimics that of isolated HCC or iCCA. Intratumoral heterogeneity leads to difficulties with pathologic diagnosis from sampling due to the possibility of an incorrect diagnosis if the biopsy specimen does not contain adequate tissue comprising both histologic components.